Analisis faktor, kesahan dan keboleh percayaan instrumen Inventori Stereotaip Multietnik Malaysia (ISMEM) - Jasmine Adela Mutang; Lailawati Madlan; Ferlis Bullare @ Bahari; Chua, Bee Seok (Persatuan Psikologi Malaysia, 2015)
This study aimed to test the validity and reliability of the Inventory of Malaysian Multi Ethnic Stereotypes (ISMEM) instrument developed by the researchers. The qualitative phase was using in-depth interviews and focus group discussions. The employment of qualitative method was to explore the concept of stereotypes among the ethnic groups. Quantitative phase involves the formation of items by themed and categorised the items that were built from the qualitative phase. A total of 1,000 university students from various ethnic groups in Malaysia were involved in the quantitative phase. Exploratory factor analysis on ISMEM has formed two main components labelled = .897-.933) and the Phenomenon Stereotypes are well accepted (α = .706-.821). Therefore, ISMEM is a reliable and valid measure. However, further studies need to be conducted in other groups of sample to further validate the instrument.